(3cJGH GdJfHjg Yf GddMf GdLdi hGdNaj aj GdbQBf hGdCdaGX GdeSJcQggs - (3CHh GdMSf Ydj Hf LYaQ Hf eMeO GdQGRj GdSYjOjs
(3ChdgG (B:s
(3GdMeO ddg fHJOF hEjGg Cf CUfa dc fHPkG ef JLhjO GddaX hCfHFc Yf HYV eG JNai Yf cKjQ efCgd GdVHW hGdBOGA s
(3BNQgG (B:s
(3hGdSGOS YTQ ef GdNjGTje hgj Gdfhf GdNajaI Je cJGH GdJfHjg HYhf Gddg hMSf Jhajbg hGdMeO ddg hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde JSdjekG cKjQoG CHOG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B8s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HBNQgG fbhd eNJdaIs
(3eUOQ GbJfGA GdCUd (B:s
(3GdRGhjI GdMeRGhjI (B_ (3GdeZQH (B(190) s
Keywords: (3GdeLGejYs